Integration of Health Education and Multimodal Learning in Enhancing Antibiotic Literacy to Prevent Antimicrobial Resistance - Zakia Asrifah Ramly; Asnurbaety Dwiyana; Maipha Deapati Arief; Anik Nur Janah; Nur Anisa (Universitas Pahlawan Tuanku Tambusai, 2025)
Antimicrobial resistance (AMR) is a growing global health threat driven by the misuse of antibiotics, particularly in areas with low antibiotic literacy. This study evaluated the impact of multimodal learning on improving antibiotic literacy among high school students in Jeneponto Regency. A total of forty-seven students from SMP Negeri 6 Tamalatea participated in a pretest-posttest design involving face-to-face sessions, printed modules, instructional videos, and role-playing activities. Data were collected via a validated questionnaire before and after the intervention. Results showed a significant increase in antibiotic literacy scores, with most students moving from low or moderate levels before the intervention to high levels afterward. Statistical analysis confirmed a strong positive correlation between the multimodal learning approach and literacy improvement. These findings demonstrate that combining various learning methods effectively engages diverse student learning styles, enhancing understanding and retention. The study supports the integration of multimodal educational strategies in school health programs to promote responsible antibiotic use and help prevent AMR from an early age.